Morphometry, physiology, biochemistry and minerals in Suaeda edulis ecotypes with diluted seawater - Ruiz-Companioni, Idael; Palacios-Espinosa, Alejandro; Murillo Amador, Bernardo; Ruiz-Espinoza, Francisco Higinio; Mazón-Suástegui, José Manuel; Beltrán-Morales, F´elix Alfredo (Ecosistemas y Recursos Agropecuarios, 2025)
Salinity is an abiotic factor that affects plant growth and development. However, some halophyte species develop mechanisms to tolerate saline conditions. The objective was to evaluate morphophysiological and biochemical characteristics, and mineral accumulation of Suaeda edulis Flores Olv. & Noguez. The experiment was conducted in a floating-root hydroponic system with a completely randomized design with a factorial arrangement. The first factor was three S. edulis ecotypes that were subjected to a second factor consisting of salinity stress (seawater diluted with Oreochromis niloticus wastewater) with four electrical conductivities (2.5, 10.0, 15.0, 30.0 dS m-1). The variables evaluated were growth parameters, chlorophyll content, water potential, protein content, ether extract and crude fiber, and mineral content. The results showed that most of the variables showed significant differences in the interaction of the factors. There is a differential response of the ecotypes to stress treatments, observing a polynomial (cubic/quartic) trend in the variables, which showed low values at low electrical conductivities, a maximum positive response at intermediate levels of electrical conductivity, suggesting optimal conditions for growth, and at high electrical conductivity, a decrease was observed in most of the variables. The differential accumulation of sodium and potassium indicates exclusion and tolerance mechanisms that vary between ecotypes. These findings highlight the potential of S. edulis to grow in environments with moderate salinity and provide information on its adaptive physiology.